(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the integration of Russian language instruction into biology education as a strategic approach to enhance students’ scientific and linguistic competence simultaneously. Drawing on interdisciplinary methods such as Content and Language Integrated Learning (CLIL), the paper emphasizes the pedagogical benefits of contextualizing biology instruction within the framework of Russian-language acquisition. It highlights how task-based learning, authentic text exposure, multimodal instruction, and language-sensitive assessment strategies can deepen students’ grasp of both biological concepts and academic Russian. Furthermore, the article addresses the sociolinguistic, cognitive, and institutional implications of bilingual science education in post-Soviet and multilingual regions, advocating for cross-disciplinary teacher training and systemic curricular support. By fostering dual literacy in science and language, the model prepares learners for higher education and global scientific participation.